Implementation of Arrangements for Ikrar Wakaf Land (AIW) in The Indonesian Waqf Law (Case in Palembang City) - Rochmiyatun, Siti; Fitriyati, Yusida (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research examines the provision of Waqf Land in Indonesia and its implementation in Palembang City. The aim is to identify obstacles in its implementation while finding solutions so that the management of waqf land can be more productive by the desires of the Waqif (Waqf Doer).The results of the study find out that the Regulation made by the Directorate General of Islamic Community Guidance Number 75/1978, which regulates the Format and Content of Endowments Pledge, contains weaknesses that may hinder the productivity of waqfland. This is indicated by the format of the W2 and W3 form models which limit the uses of the WaqfLand, giving an interpretation that the Nazir (Waqfmanager) may not add the Waqf object to other uses. In the future, the format and the substance of AIW, which become the basis for Nazirin managing the Waqf, must be made in such a way that Nazhir has the freedom to develop the use of Waqfland more productively by the wishes of the waqif and the WaqfAct. Apart from the weaknesses above, the implementation of the Ikrar Tanah WaqfAct in Palembang, especially for the Mosque waqf, have been running well and productively.